Fundamentals of electric drives - El-Sharkawi, Mohamed A. (Cengage, 2017)
"Fundamentals of electric drives, 2nd Edition presents the basic topics and fundamental concepts underlying electric machines, power electronics, and electric drives. Rather than concentrating on converters and waveform analysis while ignoring mechanical load dynamics or focusing on motor characteristics with little analysis of converters and controllers, this approach provides a complete overview ideal for EE undergraduates. Students progress through the analysis and design of a complete electric drive system with coverage of mechanical loads, motors, converters, sensing, and controllers. The author emphasizes drive applications to electric traction, robotics, and wind energy with real industry examples that make this a useful and practical reference even for professional electric drive engineers